Análise rasa de subsuperfície com radar de penetração no solo (GPR) em depósitos neógenos na praia do Atalaia (Salinas) e Aricuru (Maracanã), Nordeste do estado do Pará - SILVA, Fabrício Souza da (2019)
Geological-geophysical studies based on Ground Penetrating Radar (GPR) were carried out in the Atalaia Beach, Salinópolis district, and Aricuru village, Maracanã district, northeastern Pará. The 5m depth radar imaging in combination with sedimentological data, allowed the identification of lithofacies, layer geometry and possible tectonic structures in Neogene carbonate and siliciclastic deposits respectively related to Pirabas and Barreiras formations and quaternary sediments of the Post-Barreiras unit, accumulated in the Bragantina Platform. Previous work using GPR in the Atalaia Beach, reaching a depth of up to 13m, have shown tectonic deformation in the upper part of Pirabas Formation. We used this same technique of shallow imaging that it did not reach the layers of carbonates, the reflections showed a perfect correlation with the rhythmite and sandstone horizontal levels of the Barreiras Formation, sometimes recording shallow paleochannels. The deformation considered for carbonates in the Atalaia Beach, are not observed in the surface. Random dip bedding of the Pirabas Formation are related to the erosive action of wave and tidal currents that provide the removal of finer lithofacies interbedded with more lithified carbonate layers, generating gravitational instabilities and fractures, a typical cliff retreat process. In Aricuru where the Barreiras siliciclastic are little thick, the obtained GPR section showed a perfect correlation of reflections with carbonate horizontal levels, especially biohermite forming hardgrounds levels, extend by dozens of meters overlaid by Quaternary beach sediments. These deposits are interrupted by a normal fault, detected by the physical properties contrast of the lithofacies. The application of GPR in Neogene rocks is a important tool to obtain complementary geological observations, as well as, to guide future studies that aimed unravel the shallow substrate architecture in the coastal area of the Salgado Region.